Healthcare workers’ knowledge, attitudes, practices on post exposure prophylaxis for HIV in Dar es Salaam (Tanzania Medical Journal, 2015)
Background : Access to HIV care and treatment has improved over the past several years, but safety standards and precautions have not improved in the same proportions leading to increased risk of exposure to and transmission of HIV through occupational injury, mainly via needle stick injury. This hospital based study of 316 health care workers (HCW) in Dar Es Salaam aimed to investigate the knowledge, attitude and practices on post exposure prophylaxis for HIV exposure. Results: Occupational exposure to HIV was common among HCWs, affecting 169 out of 316 workers surveyed. The affected workers included nurses and doctors. Of the 169 HCWs exposed, 41 had taken post exposure prophylaxis (PEP). Only about one third knew the initial steps to be followed after exposure as recommended in National Guidelines. Hospitals were the major source of information on PEP. Most of the HCWs had satisfactory knowledge on PEP. Approximately fifteen percent of HCWs had used PEP and the mean time to start use of PEP was 13.5 hours. Approximately forty percent failed to use PEP for the full length of time prescribed; the main reason for the shorter duration was adverse affects associated with the antiretroviral drugs. Conclusion: There is a need to intensify education on PEP among HCWs to increase their awareness and knowledge and train HCWs to practice universal safety precautions to decrease risk of HIV transmission.